PENGARUH UPAH, INVESTASI, DAN PERTUMBUHAN EKONOMI TERHADAP PERMINTAAN TENAGA KERJA DI KABUPATEN/KOTA SUMATERA BARAT - Putri Maya; Yulhendri Yulhendri (Universitas Negeri Padang, 2019)
Abstract: One indicator used to measure economic development is employment. The huge population growth each year will certainly have an impact on increasing the number of the workforce and will certainly give meaning that the number of people looking for work will increase, along with that the workforce will also increase. This study aims to analyze the effect of wages, investment and economic growth on labor demand in West Sumatra. This study uses secondary data in the form of time series with an observation period of 2013-2017. Data obtained from the Central Statistics Agency (BPS), data analysis using the panel regression method with the program eviews. The results of this study include wages that negatively and significantly affect labor demand in West Sumatra. While investment and economic growth have a positive and significant effect on labor demand in West Sumatra. And the most dominant factor influencing labor demand in West Sumatra is the Economic Growth factor where the factor has the greatest regression coefficient among other factorsKeywords: labor, wages, investment, economic growth